Aksesibilitas Pelayanan Publik Bagi Penyandang Disabilitas di Kota Palu - Srifridayanti, Srifridayanti; Sussanti, Sussanti; Samkamaria, Samkamaria; Nurvianti, Dewi (PUBLICNESS: Journal of Public Administration Studies, 2023)
This study aims to determine efforts to fulfill the accessibility of public services for persons with disabilities in Palu City. This research uses qualitative research with a descriptive design, which is research that provides a careful description of certain individuals or groups about the circumstances and symptoms that occur. The results showed that the Palu City Government already commits to paying attention to persons with disabilities. However, in reality, it can be seen from the research results that there are still many public facilities that are not optimal in providing easy access to services for persons with disabilities. Public facilities in Palu City do not entirely ignore accessibility standards, meaning that there are public facilities that are good enough but more are not optimal, this is due to the lack of knowledge and understanding of the city government as a policy maker on the reference standards for accessibility for persons with disabilities.